2012
DOI: 10.5152/etd.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Substance, Cigarette and Alcohol Use Among High School Students in the Provincial Center of Samsun, Turkey

Abstract: GirişDünya Sağlık Örgütü'nün (DSÖ) 10-19 yaş arası olarak tanımladığı ergenler, dünyadaki her beş kişiden birini oluşturur; ergenlerin yaklaşık %85'i gelişmemiş ülkelerde yaşar (1). Türkiye'de 2010 yılı Adrese Dayalı Nüfus Kayıt Sistemi verilerine göre ergen yaş grubu nüfusu 12.846.048 (%17,4) kişidir (2). Ülkemizin de içinde olduğu DSÖ Avrupa Bölgesi'nin 21. yüzyılda ulaşmayı amaçladığı "Öncelikli 21 Sağlık Hedefi" listesinde gençlerin sağlığının geliştirilmesi hedefi ilk sıralarda gelmektedir (3). DSÖ yetişk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
1
10
0
13
Order By: Relevance
“…These results suggest that regulations related with alcohol alone are insufficient and education programs for children and families should be conducted in order to delay the age of alcohol inititation in children and adolescents. In this study, it was observed that the rate of being drunk (31.6%) was higher compared to the rate found in high school students in Istanbul in 2000 (19) and the rate found in high school students in Samsun in 2008 (10.41%) (11,14). In both studies, the rate of the students who got drunk increased as the grade got older similar to the results of our study (11,14).…”
Section: Behaviors Of Consuming Alcoholic Beveragesmentioning
confidence: 52%
See 3 more Smart Citations
“…These results suggest that regulations related with alcohol alone are insufficient and education programs for children and families should be conducted in order to delay the age of alcohol inititation in children and adolescents. In this study, it was observed that the rate of being drunk (31.6%) was higher compared to the rate found in high school students in Istanbul in 2000 (19) and the rate found in high school students in Samsun in 2008 (10.41%) (11,14). In both studies, the rate of the students who got drunk increased as the grade got older similar to the results of our study (11,14).…”
Section: Behaviors Of Consuming Alcoholic Beveragesmentioning
confidence: 52%
“…In this study, it was observed that the rate of being drunk (31.6%) was higher compared to the rate found in high school students in Istanbul in 2000 (19) and the rate found in high school students in Samsun in 2008 (10.41%) (11,14). In both studies, the rate of the students who got drunk increased as the grade got older similar to the results of our study (11,14). In the "Health Behaviour in School-aged Children Study" 2009/2010, the rate of having been drunk for at least two times in the 15-year age group was found to range between 8% (Macedonia, girls) and 57% (Lithuania, boys) (mean: 32%) (9).…”
Section: Behaviors Of Consuming Alcoholic Beveragesmentioning
confidence: 52%
See 2 more Smart Citations
“…Sample size calculation was mentioned in a group of studies some with and others without details provided (Altuner & et al, 2009;Arslan, Terzi, Dabak, & Pekşen, 2012;Canbulat & Yıldız, 2011;Ceylan et al, 2003;Doğan, 2001;Eneçcan, Şahin, Erdal, Aktürk, & Kara, 2011;Evren et al, 2014;Güler, Güler, Ulusoy, & Bekar, 2009;İnandı et al, 2009;Kara et al, 2003;Keskinoğlu et al, 2006;Ögel, Tamar, Evren, & Çakmak, 2000;Ögel et al, 2001;Ögel et al, 2004;Özyurt & Dinç, 2006;Palanci et al, 2009;Şaşmaz et al, 2006). One study sampled all students from all schools located in the center of a province (Eneçcan et al, 2011).…”
Section: Resultsmentioning
confidence: 99%